Assessing the Reproducibility of the Covid-19 Pandemic with COMOKIT: A Case Study in Ibirama, Brazil - Rosa, Denilson Laucsen da; Santos, Fernando (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2025: Anais do XIX Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações, 2025)
Agent-based models have proven to be effective alternatives for simulating the spread of infectious diseases, as they account for the heterogeneity and interactions among individuals. The Covid-19 Modeling Kit (COMOKIT) is one such model, designed to study Covid-19 containment policies. Implemented in the GAMA platform, COMOKIT was originally calibrated to simulate Covid-19 in a community in Vietnam. This paper investigates whether COMOKIT can reproduce the Covid-19 dynamics observed in the municipality of Ibirama, Santa Catarina, Brazil. Reliable sources were used to obtain demographic, geographic, and epidemiological data, and simulations were conducted under different configurations, including scenarios with and without lockdowns, testing, and hospitalizations. The results show that, despite careful parameterization, COMOKIT was unable to reproduce the number of cases and deaths observed in Ibirama during the first three months of the pandemic. These findings highlight limitations in applying the model to Brazilian municipalities without additional calibration, suggesting the need for further studies using more accurate data.